Regulation of nc886 (vtRNA2-1) RNAs is associated with cardiometabolic risk factors and diseases - Rajić, Sonja; Delerue, Thomas; Ronkainen, Justiina; Zhang, Ruiyuan; Ciantar, Joanna; Kostiniuk, Daria; Mishra, Pashupati P.; Lyytikäinen, Leo-Pekka; Mononen, Nina; Kananen, Laura; Peters, Annette; Winkelmann, Juliane; et al. (Springer Science and Business Media LLC, 2025)
Non-coding 886 (nc886, vtRNA2-1) is a polymorphically imprinted gene. The methylation status of this locus has been shown to be associated with periconceptional conditions, and both the methylation status and the levels of nc886 RNAs have been shown to associate with later-life health traits. We have previously shown that nc886 RNA levels are associated not only with the methylation status of the locus, but also with a genetic polymorphism upstream from the locus. In this study, we describe the genetic and epigenetic regulators that predict lifelong nc886 RNA levels, as well as their association with cardiometabolic disease (CMD) risk factors and events. We utilised six population cohorts and one CMD cohort comprising 9058 individuals in total. The association of nc886 RNA levels, as predicted by epigenetic and genetic regulators, with CMD phenotypes was analysed using regression models, with a meta-analysis of the results. The meta-analysis showed that individuals with upregulated nc886 RNA levels have higher diastolic blood pressure (beta = 0.07, p = 0.008), lower HDL levels (beta = - 0.07, p = 0.006) and an increased incidence of type 2 diabetes (OR = 1.260, p = 0.013). Moreover, CMD patients with upregulated nc886 RNA levels have an increased incidence of stroke (OR = 1.581, p = 0.006) and death (OR = 1.290, p = 0.046). In conclusion, we show that individuals who are predicted to present elevated nc886 RNA levels have poorer cardiovascular health and are at an elevated risk of complications in secondary prevention. This unique mechanism yields metabolic variation in human populations, constituting a CMD risk factor that cannot be modified through lifestyle choices.